2012
DOI: 10.1002/ece3.429
|View full text |Cite
|
Sign up to set email alerts
|

Invasion history and demographic pattern of Cryphonectria hypovirus 1 across European populations of the chestnut blight fungus

Abstract: We reconstructed the invasion history of the fungal virus Cryphonectria hypovirus 1 (CHV-1) in Europe, which infects the chestnut blight fungus Cryphonectria parasitica. The pattern of virus evolution was inferred based on nucleotide sequence variation from isolates sampled across a wide area in Europe at different points in time. Phylogeny and time estimates suggested that CHV-1 was introduced together with its fungal host to Europe and that it rapidly colonized the central range along the south facing slopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 68 publications
4
53
1
Order By: Relevance
“…This change was most apparent following the re‐isolation of virus‐infected isolates from lesions formed on the seedlings, and the same isolates tended to form fewer stromata, were associated with less epicormic growth in the infected plant material and produced smaller lesions. It has previously been reported that mycovirus infection (hypovirulence) in C. parasitica is associated with loss of colony pigmentation and reduced sporulation . However, it was notable in our study that the virus‐infected UK isolates did not have a white colony phenotype and slower growth on initial screening, although low levels of CHV‐1 could be detected (original nanograms per microlitre detections of 9.9 for L‐6 and 9.2 for Db‐1), but only became apparent on re‐isolation from inoculated host material when the virus concentration was also found to have increased (respective concentrations of 31.5 ± 5.7 and 30.2 ± 25.5 ng μL −1 ).…”
Section: Discussionmentioning
confidence: 46%
“…This change was most apparent following the re‐isolation of virus‐infected isolates from lesions formed on the seedlings, and the same isolates tended to form fewer stromata, were associated with less epicormic growth in the infected plant material and produced smaller lesions. It has previously been reported that mycovirus infection (hypovirulence) in C. parasitica is associated with loss of colony pigmentation and reduced sporulation . However, it was notable in our study that the virus‐infected UK isolates did not have a white colony phenotype and slower growth on initial screening, although low levels of CHV‐1 could be detected (original nanograms per microlitre detections of 9.9 for L‐6 and 9.2 for Db‐1), but only became apparent on re‐isolation from inoculated host material when the virus concentration was also found to have increased (respective concentrations of 31.5 ± 5.7 and 30.2 ± 25.5 ng μL −1 ).…”
Section: Discussionmentioning
confidence: 46%
“…Two main reasons account for this less dramatic course of the epidemics. CHV-1 has successfully spread across Europe and become established in many C. parasitica populations (Bryner, Rigling, & Brunner, 2012;Heiniger & Rigling, 1994;Milgroom & Cortesi, 2004). Secondly, in Europe, the chestnut blight fungus became itself infected by a mycovirus, named Cryphonectria hypovirus 1 (CHV-1) that reduces virulence (hypovirulence) and sporulation of the infected C. parasitica strains (Anagnostakis, 1982;Dawe & Nuss, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic studies applied to mycoviruses (Pearson et al 2009;Ghabrial and Suzuki 2009;Roossinck et al 2010;Xie and Jiang 2014) and fungi (see next section) point to new hyperparasite or fungal antagonist candidates. Some mycoviruses have followed the route of invasion of their invasive fungal hosts and have been first detected in the introduced range of their hosts (Bryner et al 2012;Feau et al 2014;Voth et al 2006;Schoebel et al 2014;Martinez-Alvarez et al 2014). However, according to the enemy release hypothesis (Mitchell and Power 2003), hyperparasites are expected be more frequent in the native range of their hosts than elsewhere, and thus, systematic searches should be concentrated in these areas (Roderick and Navajas 2003;Hale et al 2014;Ridout and Newcombe 2015).…”
Section: Hyperparasitism Of Fungal Pathogens: a Poorly Understood Butmentioning
confidence: 99%
“…The horizontal transmission of mycoviruses is controlled by the fungal vegetative incompatibility system, which, until recently, was thought to impede virus transmission in populations. However, some mycoviruses have a global distribution [e.g., CHV1 (Bryner et al 2012), Gremmenellia virus ]. Recent results showed that in situ transmission rates of CHV1 are higher than in vitro studies had suggested (Carbone et al 2004;Brusini and Robin 2013).…”
Section: Hyperparasitism Of Fungal Pathogens: a Poorly Understood Butmentioning
confidence: 99%